Is the development of liquid biopsy for the early detection and the monitoring of breast cancers on its way of overtaking mammography? - Mansour, Hicham; Nejjari, Chakib; Incitti, Roberto; Anouar, Naima; Ouhajjou, Abdelhak (Frontiers in Medicine, 2024)
Mammography, as of today, is used as a gold standard for screening, diagnosing, and monitoring breast cancer (BC). While overall beneficial, it presents several downsides, such as limitations in accuracy, relatively high costs, and dependence on heavy infrastructure, greatly limiting accessibility for the entire global target population. There is currently no established alternative to mammography, and overcoming this major challenge is a hot topic in research and technology. One avenue for tackling this issue is the development of highly sensitive and specific non-invasive blood tests for the early diagnosis and follow-up of breast cancer. This paper discusses the limitations of mammography and recapitulates the blood tests already available, those under development, and future developments in this field.